2015
DOI: 10.1039/c4ob02096k
|View full text |Cite
|
Sign up to set email alerts
|

Indole-based novel small molecules for the modulation of bacterial signalling pathways

Abstract: Gram-negative bacteria such as Pseudomonas aeruginosa use N-acylated L-homoserine lactones (AHLs) as autoinducers (AIs) for quorum sensing (QS), a major regulatory and cell-to-cell communication system for social adaptation, virulence factor production, biofilm formation and antibiotic resistance. Some bacteria use indole moieties for intercellular signaling and as regulators of various bacterial phenotypes important for evading the innate host immune response and antimicrobial resistance. A range of natural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…This result does not agree with the findings by Caputo et al (2015); the considerably higher value of the molecule confirms the previous hypothesis that it is plausible that an indigo-derivative is formed by colored P. fluorescens strains. Recently, a study reported the involvement of indigo-derivative molecules as modulators in bacterial signaling pathways (Biswas et al, 2015). This result suggests a potential function for the blue pigment.…”
Section: Biochemical Characterization Of the Blue Pigmentmentioning
confidence: 96%
“…This result does not agree with the findings by Caputo et al (2015); the considerably higher value of the molecule confirms the previous hypothesis that it is plausible that an indigo-derivative is formed by colored P. fluorescens strains. Recently, a study reported the involvement of indigo-derivative molecules as modulators in bacterial signaling pathways (Biswas et al, 2015). This result suggests a potential function for the blue pigment.…”
Section: Biochemical Characterization Of the Blue Pigmentmentioning
confidence: 96%
“…For example, indole-derived flustramine and pyrroloindoline triazole amides inhibited biofilm formation by Acinetobacter baumannii, E. coli, and methicillin-resistant S. aureus more efficiently than did indole [46,67] and 2-aminobenzimidazole inhibited biofilm formation by P. aeruginosa [68]. In another study, the brominated furanone motif and indole were combined to produce desformylflustrabromine, which inhibited biofilm formation by S. aureus and E. coli [45], and the N-acylated L-homoserine lactone motif and indole were combined to inhibit P. aeruginosa QS [69]. Recently, two review papers described indole-containing small molecules that modulate bacterial behaviors and the synthetic approaches they used [29,30].…”
Section: Antivirulence Activities Of Indoles Against Non-indole-produmentioning
confidence: 97%
“…Other furanone analogs have been developed including S-phenyl-l-cysteine sulfoxide and diphenyl disulfide [66] and tetrazole derivatives [67]. Furthermore, synthetic LasR derivatives have been developed such as indole derivatives, non-AHL-like antagonists [68], the synthesized azines derivatives, 4-(alkyloxy)-6-methyl-2H-pyran-2-one [69] and aspirin [70]. Triphenyl hybridγ-butyrolactones and cyclopentanones derivatives are potent inhibitors of LuxR [71].…”
Section: Elimination Of the Qs Signal-receptor Interactionmentioning
confidence: 99%